DISEMINASI METODE PEMBELAJARAN UNTUK GURU DI SEKOLAH DENGAN AKSES TERBATAS: UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA - Anggun Pertiwi; Devi Marganing Tyas; Tia Latifatu Sadiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The quality of learning in schools with limited access still faces challenges of inadequate facilities and monotonous teaching methods. This community service disseminated interactive and contextual teaching methods to 10 teachers in Tirtajaya District using the Asset Based Community Development (ABCD) approach. Implementation consisted of seminars, discussions, and practical simulations. Evaluation through questionnaires and reflections indicated improved pedagogical competence, a shift in teaching paradigms, and commitment to apply methods such as Video Learning, Based on Picture, True or False, Modelling, and Project-Based Learning. This activity contributed to enriching teaching strategies in schools with limited resources.